Quality and validity in animal research - Olsson, Anna (Henry Stewart Talks, 2016)
Quality and validity in animal model research are issues of scientific and ethical relevance, High-quality research with high validity requires expertise in biological and clinical aspects in combination with knowledge in experimental design, Contemporary research using systematic reviews and meta analysis have shown problems with the experimental design of many animal studies, As a result of design shortcomings, results from many animal studies are not reliable, This lecture addresses basic aspects of quality and validity of animal research using examples